Andando com os Arara - Belezini, Eduardo Henrique Capelli (2017)
Looking for how to make antropology, I started to construct the text following the pathway, stopping some moments for reflexion about the tracks that were appearing. On the long way to school I found Altamira-PA, and then the Arara from Laranjal, whom I decided to follow, learning with them how to relation on their rhythms and references. Upon the tasks, I saw how to make collectives, joining myself on the relations, I saw leadderships appearing amog the ethics of conduct guided by moralities. Between the new and the old or amid the “good” and the “evil”, the “One” and the multiple seens to be the terms of the relation. Coming back from religious interchanges, now there are Arara that are brother before Christe, problematizing the sociality amid the “good” and the “evil”, between God and the Devil, putting in check the xaman, the leaderships and the xaman system: with which force? Creating the community, beyond the good and the evil, the question is the agency – with the evangelicals missionaries of ALEM, with the evangelicals Waiwai, and with the State. Travelling with the Arara, I have been inserted on the politics and aesthetics relations of this coletive, with whom I walked with, seen about being and the appearance, what involves the “other”. Becoming Ugoro´gmo (we all, us), in the middle of the era of the projects of the Basic Enviromental Plan, in the midst of the evangelicals missionaries, Funai, and the school, they become another? In ugorog´mo way, the question seens to be of the updating, of the restart of sociality, conducted on the generosity ethic, controled by the morality of doing-shame, of exposing the other to the sociality, which contains the Arara subject on a appearance community, that expand on the aldeia space to the ways that are percurssed, which I falled.